Análise da relação entre a tecnologia da informação e comunicação e a capacidade organizacional em organizações sem fins lucrativos - Marco, Daiana de (2019)
Around the world it is possible to see the actions of non-profit organizations (OsFil) in favor of society, causing changes in local, regional, national and international reality. OsFil are organizations that do not have as main objective the economic and financial result. Due to the important role that these organizations play in society, study is still needed to contemplate them. In this sense, the present research seeks to broaden the approach of organizational capacity and Information and Communication Technology (ICT), within non-profit organizations. Organizational capacity is understood as processes, practices, people, available resources that assist the organization in achieving the organizational mission. Information and Communication Technology has provided the OsFil new means of social participation, also the use of technology is a vital condition to promote innovation and give sustainability to these organizations. The research aimed to analyze the relationship between ICT and the elements of organizational capacity in OsFil. For this, an online survey was used, which used an already validated organizational capacity model. And for the evaluation of ICT was built a specific instrument for non-profit organizations. A total of 82 questionnaires were analyzed. There were also 7 interviews with OsFil managers from different states of the federation. The main source of appeal cited by the OsFil was the donations of volunteers (individuals) with 79.3%. With regard to social networks used by the Fil, Facebook (93.8%) is the most used. In the interviews WhatsApp had a prominence in the operationalization of the activities of OsFil, it is also used by 54.3% of the organizations that answered the survey. The most obvious relationship was between ICT and external communication. The dimensions of mission orientation and financial management were less related to ICT. In the correlation, the associations between the elements of organizational capacity and ICT are moderate and positive. As a suggestion of future research, it is suggested the validation in the national context of the instrument proposed by Shumate et al. (2017) and the ICT tool. In addition, other online questionnaire application strategies should be designed for this particular audience.